Pengaruh Media Konkret Terhadap Hasil Belajar Matematika Siswa Kelas 2 SD Negeri Bojong 3 Kota Tangerang - Fitriana, Ratih; Amaliyah, Aam; Unaenah, Een (Peneliti.net, 2024)
This study aims to determine whether or not there is an influence of Concrete media on Student Learning Outcomes in Mathematics. The method used in this study is Quasi Experimental and Conventional. The hypothesis put forward in this study is: